Teaching Competence of Public School Teachers in the Light of the Philippine Professional Standards for Teachers - Rodelyn E. Malunes; Dexter Paul D. Dioso (Philippine Social Science Journal, 2020)
The teaching competence of teachers is highly regarded as the core of every educational endeavor. Educators worldwide are greatly challenged to gradually develop a more complex teaching competence due to the demand for highly skilled graduates in the global market. Consequently, the Department of Education adopted the Philippine Professional Standards for Teachers (PPST) as a quality assurance tool in implementing the K to 12 Curriculum. The domains of the PPST comprised the complete competency that guarantees a manifestation of globally best teaching practices. Hence, the paper assessed the level of teaching competence of public elementary school teachers in the Division of Bacolod City during the school year 2019-2020, when grouped according to educational attainment, teaching experience, and assessor's designation. Also, it analyzed whether a significant difference exists in the areas of teaching competence and demographics.